2021
DOI: 10.3390/app11125363
|View full text |Cite
|
Sign up to set email alerts
|

Perspectives on Cathodes for Protonic Ceramic Fuel Cells

Abstract: Protonic ceramic fuel cells (PCFCs) are promising electrochemical devices for the efficient and clean conversion of hydrogen and low hydrocarbons into electrical energy. Their intermediate operation temperature (500–800 °C) proffers advantages in terms of greater component compatibility, unnecessity of expensive noble metals for the electrocatalyst, and no dilution of the fuel electrode due to water formation. Nevertheless, the lower operating temperature, in comparison to classic solid oxide fuel cells, place… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(30 citation statements)
references
References 200 publications
(240 reference statements)
0
25
0
Order By: Relevance
“…This strategy is constantly developing due to the design of new electrolyte materials, 121,138–141 novel thin-film technologies, 32,142,143 and innovative highly active electrode systems. 144–148…”
Section: Electronic Transport Of Individual Proton-conducting Materialsmentioning
confidence: 99%
“…This strategy is constantly developing due to the design of new electrolyte materials, 121,138–141 novel thin-film technologies, 32,142,143 and innovative highly active electrode systems. 144–148…”
Section: Electronic Transport Of Individual Proton-conducting Materialsmentioning
confidence: 99%
“…A couple of reviews focusing on cathode materials for PCFCs are available in literature. [139,[171][172][173][174][175][176] Some examples are highlighted below.…”
Section: H + -Lt-sofc or Pcfcmentioning
confidence: 99%
“…Recently, it has been shown that effective cathodes for proton-conducting SOFCs operating at low and intermediate temperatures are Ba(Ce,Zr)O 3 -based solid solutions doped with transition elements in high concentration. These phases demonstrate excellent chemical compatibility with typical proton-conducting solid electrolytes due to the similarity of their compositions [ 43 , 44 ]. These compounds belong to the triple-conducting oxides (TCOs) [ 45 , 46 , 47 ], in which transport species are simultaneously protons, oxygen ions, and electrons (holes).…”
Section: Cathode Materials For It–sofcs: Past Present and Futurementioning
confidence: 99%
“…The advantage of TCOs as cathode materials for proton-conducting SOFCs is that both protons from the solid electrolyte and oxygen species adsorbed from the air may migrate through the bulk and over the surface of the cathode, which extends the reaction area over the whole electrode. We should note that LODPs, such as Ln Ba 0.5 Sr 0.5 Co 1.5 Fe 0.5 O 5+δ ( Ln = Pr, Nd), when used as cathodes for proton-conducting SOFCs, also belong to the class of TCOs [ 9 , 44 ]. According to [ 48 ], triple conductivity in LODPs can appear due to the formation of impurity phases, which should be taken into account for the development of new TCOs.…”
Section: Cathode Materials For It–sofcs: Past Present and Futurementioning
confidence: 99%